2016
DOI: 10.1158/1078-0432.ccr-15-2973
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of SOAT1 Suppresses Glioblastoma Growth via Blocking SREBP-1–Mediated Lipogenesis

Abstract: Purpose Elevated lipogenesis regulated by sterol regulatory element-binding protein-1 (SREBP-1), a transcription factor playing a central role in lipid metabolism, is a novel characteristic of glioblastoma (GBM). The aim of this study was to identify effective approaches to suppress GBM growth by inhibition of SREBP-1. As SREBP activation is negatively regulated by endoplasmic reticulum (ER) cholesterol, we sought to determine whether suppression of sterol O-acyltransferase (SOAT), a key enzyme converting ER c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
280
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(297 citation statements)
references
References 50 publications
14
280
0
3
Order By: Relevance
“…Our previous studies have revealed that GBM growth is highly dependent on SCAP/SREBP-1 signaling (Cheng et al, 2015; Geng et al, 2016; Guo et al, 2009b; Guo et al, 2011). We asked whether miR-29 transfection was able to inhibit GBM cell growth through suppressing SCAP/SREBP-1-regulated lipogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have revealed that GBM growth is highly dependent on SCAP/SREBP-1 signaling (Cheng et al, 2015; Geng et al, 2016; Guo et al, 2009b; Guo et al, 2011). We asked whether miR-29 transfection was able to inhibit GBM cell growth through suppressing SCAP/SREBP-1-regulated lipogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence shows that lipid metabolism is also reprogrammed in malignancies to support rapid tumor growth (Bell and Guo, 2012; Geng et al, 2016; Guo et al, 2013; Guo et al, 2014; Menendez and Lupu, 2007; Ru et al, 2013). In particular, our recent work has revealed that oncogenic EGFR signaling activates lipid metabolism via upregulation of SCAP/SREBP-1 signaling (Cheng et al, 2015; Guo, 2016; Guo et al, 2009b; Guo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that SCAP/SREBPs play important roles in malignancies, connecting oncogenic signaling to lipid metabolism alterations, leading to rapid tumor growth (Figure 1) [13, 60, 61, 7678, 80, 82]. Multiple studies have suggested that SCAP/SREBPs are very promising molecular targets in cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the correlations between SREBP-1c and neural oncogenesis have also been extensively investigated, in which aberrantly increased expression of SREBP-1c is found inside glioblastoma tissues, which positively relates to tumor growth and local spread by stimulating its downstream targets of ACC and FASN [134]. Additionally, upregulation of SOAT1 [135] and N-glycosylation of SCAP jointly contribute to SREBP-1c activation [136], while miR-132 suppressively targets SREBP-1c and diminishes its oncogenic properties in glioma cells [137]. In summary, based on current literatures, SREBP-1c targeted therapy has a bright future among cancer patients, especially for those with lipid-induced malignancies.…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%